Kota Qom Sebagai Pusat Pendidikan Madzhab Syi’ah: Sejarah dan Perkembangannya - El-Razy, KM. Ridho; Asari, Hasan; Badaruddin, KMS.; Zailia, ST; Fahira, Dina (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Sensitive issues of the mazhaban between Sunni and Shi'a are increasingly rife in filling the information space of Indonesian society, especially after the outbreak of the Syrian Civil War. In addition, Indonesian students who graduated from the city of Qom, Iran, are considered to be the newest generation of Shiites who have a mission to spread syi'ahism and are often in conflict with other groups. This paper attempts to answer the formulation of the problem,